Comparison of biomass production from algae Spirogyra hyalina and Spirogyra peipingensis. Issue 3 (4th May 2017) - Sulfahri,; Amin, Mohamad; Sumitro, Sutiman Bambang; Saptasari, Murni
ABSTRACT: This study aimed to determine the effects of the growth medium, water levels and incubation period on Spirogyra hyalina and Spirogyra peipingensis biomass. Completely randomized design (CRD) was used by varying the nutritional composition, water levels and incubation period. Culture was performed using a 12 h:12 h light:dark cycle using a TL 36 W fluorescent lamp with 3000 lux light intensity. The results show that the growth of the alga Spirogyra hyalina was faster than that of Spirogyra peipingensis . The highest yield obtained for Spirogyra hyalina was on day 10, whereas the highest yield obtained for Spirogyra peipingensis was on day 15. Both algae, i.e. Spirogyra peipingensis and Spirogyra hyalina, grew best in 20 cm of water level using Sulfahri-01 medium containing a high level of nitrogen.